2005
DOI: 10.1016/j.cell.2005.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of Oocyte Cell Death through the CaMKII-Mediated Phosphorylation of Caspase-2

Abstract: Vertebrate female reproduction is limited by the oocyte stockpiles acquired during embryonic development. These are gradually depleted over the organism's lifetime through the process of apoptosis. The timer that triggers this cell death is yet to be identified. We used the Xenopus egg/oocyte system to examine the hypothesis that nutrient stores can regulate oocyte viability. We show that pentose-phosphate-pathway generation of NADPH is critical for oocyte survival and that the target of this regulation is cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
252
3
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(273 citation statements)
references
References 52 publications
16
252
3
2
Order By: Relevance
“…108 In Xenopus oocytes, CamKIImediated phosphorylation of caspase-2 appears to prevent its activation. 111 These data are consistent with a model that predicts that the main event in caspase-2 activation is precursor dimerisation that is prevented in healthy cells by phosphorylation of caspase-2. Whether this is a general mechanism of caspase-2 activation or limited to specific cell death signalling remains to be determined.…”
Section: The Apoptotic Caspases S Kumarsupporting
confidence: 88%
See 1 more Smart Citation
“…108 In Xenopus oocytes, CamKIImediated phosphorylation of caspase-2 appears to prevent its activation. 111 These data are consistent with a model that predicts that the main event in caspase-2 activation is precursor dimerisation that is prevented in healthy cells by phosphorylation of caspase-2. Whether this is a general mechanism of caspase-2 activation or limited to specific cell death signalling remains to be determined.…”
Section: The Apoptotic Caspases S Kumarsupporting
confidence: 88%
“…106 Caspase-2 has also been shown to be necessary for TRAIL-mediated, 107,108 heat shock (HS)-induced apoptosis, 109,110 as well as oocyte cell death. 111 Recently, caspase-2 was shown to associate with Fas/CD95 DISC and get activated in that complex, but apparently not required for CD95-induced cell death. 112 Caspase-2 activation occurs rapidly and acute ablation of caspase-2 in a multitude of cell lines inhibits apoptosis in response to a range of stimuli including anticancer drugs.…”
Section: The Apoptotic Caspases S Kumarmentioning
confidence: 99%
“…However, this needs to be directly verified using a catalytically inactive mutant of hexokinase. Other investigators have demonstrated that 2-deoxyglucose-6-phosphate, generated via the action of hexokinase, can be metabolized via the pentose phosphate pathway (PPP) in quantities sufficient to support redox coupling critical for cell survival (Le Goffe et al, 1999Goffe et al, , 2002 and redox coupling between this pathway and caspase-2 activation has also recently been described (Nutt et al, 2005), so potential metabolic contributions distal to glucose phosphorylation cannot be excluded (see below).…”
Section: Mitochondrial Hexokinases As Downstream Effectors Of Growth mentioning
confidence: 99%
“…It was subsequently shown that NADPH leads to the specific inhibition of caspase-2 via phosphorylation of its prodomain. It appears that NADPH activates CaMKII, which phosphorylates a serine residue in the prodomain of caspase-2 and thereby inhibits its activity (Nutt et al, 2005). Whether or not gluconeogenesisderived glucose-6-phosphate can serve a similar role in tissues such as the liver remains to be examined.…”
Section: Gsh Peroxide Inactivationmentioning
confidence: 99%
“…45 Caspase-2 is also actively imported into the nucleus via a nuclear localization sequence (NLS) located in the prodomain. 7,8 Caspase-2 activation has been shown to be regulated by phosphorylation mediated by various kinases, including calcium/calmodulin-dependent protein kinase II (Ser164), 47 protein kinase CK2 (Ser157) 48 and cyclin-dependent kinase 1 (Ser340). 49 …”
Section: Caspase-2 -The Anti-cancer Connectionmentioning
confidence: 99%